2020
DOI: 10.1155/2020/8714768
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Quality of Life of Epileptic Patients in Ethiopia

Abstract: Background. Patients with epilepsy are at an increased risk of poor quality of life. Purpose. We aimed at assessing the quality of life and its determinants among epileptic patients at University of Gondar Referral Hospital (UoGRH), Ethiopia. Methods. Institution based cross-sectional study was conducted on epileptic patients on follow up at UoGRH from January 15 to April 15, 2017. Information including socio-demographic profile and diagnosis was extracted from medical records and patients. Quality Of Life In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
5
9
1
Order By: Relevance
“…This finding is consistent with study findings from Jimma University (49.7%) and Addis Ababa at Amanuel specialized hospital (45.8%) [ 27 , 28 ]. It is also in line with a study conducted at the University of Gondar Referral Hospital which has revealed that 44.2% of participants were found to have a poor quality of life [ 31 ]. Researchers in Italy have reported a consistent finding that 43.3% of patients had poor quality of life at a health institution study [ 32 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This finding is consistent with study findings from Jimma University (49.7%) and Addis Ababa at Amanuel specialized hospital (45.8%) [ 27 , 28 ]. It is also in line with a study conducted at the University of Gondar Referral Hospital which has revealed that 44.2% of participants were found to have a poor quality of life [ 31 ]. Researchers in Italy have reported a consistent finding that 43.3% of patients had poor quality of life at a health institution study [ 32 ].…”
Section: Discussionsupporting
confidence: 87%
“…Having moderate to severe anxiety and depression, and other co-morbidities resulted in decreased quality of life in epileptic patients. This finding is supported by studies conducted in China [ 52 ], Ethiopia [ 31 , 49 ], and Kenya [ 53 ]. This could be due to the effect of these problems on quality of life, particularly, in the domains of lethargy/fatigue, and emotional well-being [ 53 ].…”
Section: Discussionsupporting
confidence: 70%
“…In our study self-assessment of patients about their lives was good 31.1 % (in score language 10/10), in Ethiopia more than the half have good quality of life (54.8%) which is higher than our study, this results inspite of we have higher educational level so the problem may be overall satisfaction of patients about quality of life related to the health system that patients dealing with and to lesser extent to the awareness of the patients [24,30].…”
Section: Discussioncontrasting
confidence: 64%
“…Although Sudanese educational levels are generally higher, the impacts are still apparent. The lower self‐assessment/evaluation among the Sudanese patients may be attributed to the overall satisfaction of the patients with the healthcare system and the QOL factors related to it, in addition to the general awareness of the patients (Abadiga et al., 2019 ; Muche et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%